This plaza is mine: Decoding places with space syntax methodology - Guerreiro, R. (2022)
A place is a meaningful location, a space with a distinct character where life occurs. A place is an important source of our identity - a key to who we are. Our identity depends on our belonging to places. What is the difference between space and place? How is that a space becomes a place, a meaningful location with a sense of belonging? Is there any method which explain patterns and properties of space which are responsible for the generation of places in cities and buildings? Space Syntax is a method coined by Hillier and Hanson (1984) which correlates social content with spatial content of places. By understanding the relationship between spatial affordance and people behavior, this method can explain, in an analytical way, how a space works. In this presentation I propose to analyse the sense of place and self that we encountered in the plaza of Palazzo Adriano, the Sicilian village represented in the film of Giuseppe Tornatore "Cinema Paradiso" (1988), using space syntax methodology for decoding place attachment as well our sense of belonging to a place and a time that does not exist anymore.